My autobiography - Chaplin, Charlie (Penguin classics., 2003)
Saved from a life of hardship by his comic genius, Charlie Chaplin went on to win the hearts of nations with his films. He was born into a theatrical family, and his father died of drink while his mother, unable to bear the poverty, suffered bouts of insanity. Despite his tragic childhood, his gift for making people laugh was soon recognized and he embarked on a film-making career that would bring him immeasurable success, as well as controversy, particularly in the United States. Chaplin's immortal creation, the tramp, blended humour with pathos and classic films such as "City Lights", "The Great Dictator" and "Limelight" left audiences laughing through their tears. Yet Chaplin had to survive the coming of sound and fight political and sexual censorship and state persecution on his way to becoming a screen legend. This is his autobiography which is reissued to coincide with the release of the film "Chaplin" by Richard Attenborough.